Atomic-scale properties of jogs along 1/2〈110〉1¯10 edge dislocations in MgO. (May 2020) - Zhai, Jian-Hui; Hirel, Pierre; Carrez, Philippe
Graphical abstract: Abstract: We report atomic-scale simulations of the structure and formation energies of jog pairs on 1 / 2 〈 110 〉 1 ¯ 10 edge dislocations in magnesium oxide (MgO). The atomic configurations of elementary jogs of height 1 / 4 [ 1 ¯ 10 ] and super-jogs of height 1 / 2 [ 1 ¯ 10 ] are fully characterized showing that stable jogs spread in 111. Besides, our simulations confirm that elementary jogs carry an electric charge ± q /2 where q is the charge of a Mg ion, while super-jogs are charge-neutral. The computation of the formation energy reveals the predominance of charged elementary jogs. This offers new insight into the mechanisms for dislocation climb in MgO.